Literature Review: Pengaruh Bayam Hijau (Amaranthus hybridus L.) terhadap Panjang Badan, Rasio Kepala dan Panjang Badan, Aktivitas Embrio, dan Motilitas pada Zebrafish Stunting - Israyani, Kartika Wahyu; Khotimah, Husnul; Jannah, Miftahul (Journal of Issues in Midwifery, 2023)
Stunting is a failure to achieve physical development based on height for age (Z-score <-2 SD). Environmental factors such as exposure to pesticides can affect growth and development. One type of pesticide that is toxic to embryos is rotenone because its exposure can increase the production of ROS. The antioxidant content in green spinach (Amaranthus hybridus L.) can reduce ROS production. This study aimed to determine the effectiveness of green spinach extract on body length, head ratio and body length, embryo activity, and motility in the stunting model of zebrafish larvae exposed to rotenone. This study uses a literature review method by reviewing a number of literatures that match the inclusion criteria. Based on the 11 journals that were examined, 4 journal stated that rotenone can cause oxidative stress in zebrafish that can cause stunting. 3 journals state that green spinach contains good antioxidants and anti-inflammatory. From 11 journals, 6 journals discuss the body length in zebrafish stated that the use of antioxidants can increase body length rotenone-induced zebrafish. In 3 journals discussing the motility of zebrafish, it was stated that giving antioxidants was able to increase the motility of zebrafish induced by rotenone. In one journal that discussed the activity of zebrafish embryos, it was stated that giving antioxidants could normalize embryo activity which can be seen through embryonic tail flick activity. In conclusion, the administration of antioxidants caused an increase in body length, motility and normalization embryonic activity in rotenone-induced zebrafish. Keywords: Green spinach (Amaranthus hybridus L.), head ratio, body length, embryo activity, zebrafish, stunting, rotenone.